THE EFFECTIVENESS OF EDMODO IN INCREASING STUDENTS’ WRITING SKILL IN RECOUNT TEXT - Nanik Sri Rahayu (Pusat Pengembangan Bahasa IAIN Tulungagung, 2015)
Writing is considered as the most difficult skill for language learners to master. Language learners need to pay attention to higher level skills of planning, and organizing as well as lower level skills of spelling, punctuation, word choice, and so on. Within the rapid changes in technology, the use of ICT has largely influenced the way learners write. The well-known ICT such social networks also have been widely used by learners across the globe to shape their writing. This study examines the use of one of social networks which is specifically designed for educational purpose, Edmodo, to increase the first graders’ skill in composing recount text. The finding of the study showed significant differences between the result of pretest and posttest. The mean of post-test scores (80.5) is larger than the mean of pre-test scores (71.3). From statistical calculation, it was confirmed that the value of (-3.538) is larger than (-2.306). Also, the way to test whether the null hypothesis could be rejected was by comparing p-value with the standard level of significance, 0.05. The convention to reject the null hypothesis is that when the p-value of the obtained statistics is less than 0.05 (Balnaves & Calputi, 2001). The finding showed that p-value was less than 0.05 (0.006 < 0.05). Thus, there was enough evidence indicating that the null hypothesis could be rejected, and it could be concluded that using Edmodo was effective to increase students’ writing skill in recount text.